CLINICAL PRESETATIONS AND COMPLICATIONS ASSOCIATED WITH TUBAL RUPTURE IN PATIENTS WITH TUBAL ECTOPIC PREGNANCY - Qazi, Qudsia; Akhtar, Zubaida; Khan, Kamran (Journal of Postgraduate Medical Institute, 2011)
and short term maternal morbidity and mortality in cases of tubal ectopic pregnancy presenting to a tertiary care teaching hospital. Methodology: Results: Conclusion: The most common risk factor was PID and the most common presenting complaint was abdominal pain and amenorrhea. The mean age of the sample was 29.50+10.50. Among the etiologic factors, PID was (14%), previous ectopic (4%), ovulation induction (4%) and IUCD insertion (2%). Common clinical features were abdominal pain (90%), amenorrhea (84%), vaginal bleeding (70%), shock (32%). Clinical signs raising suspicion of tubal rupture were shock (36.3%), anemia (86.3%) and irregular mass in pouch of douglas (88.6%). Diagnosis was made clinically (92% cases) and abdominal USG with positive findings (92.5% cases). Laparotomy showed ruptured tube in 88% cases, of which 88% had rupture of ampullary region. Surgical procedures done were salpingectomy for 97% and salpingoophrectomy for 7% of ruptured tubal ectopics. Short term morbidities were shock (32%), peritonitis (32%) and severe anemia (10%). No maternal mortality was recorded. This was a descriptive study of 50 cases of tubal ectopic pregnancy; both ruptured and unruptured, presented at Khyber Teaching Hospital Peshawar from September 2002 to December 2003. Detailed history regarding age, parity, presenting features, past medical and surgical history and history regarding risk factors was taken. Operative findings regarding surgical procedures were noted. Data collected was analysed on SPSSv.10 and chi square test was used as a test of significance.